Expertise in Clinical Psychology. The Effects of University Training and Practical Experience on Expertise in Clinical Psychology - Vollmer, Sabine; Spada, Hans; Caspar, Franz; Burri, Salome (Frontiers in Psychology, 2013)
How do university training and subsequent practical experience affect expertise in clinical psychology? To answer this question we developed methods to assess psychological knowledge and the competences to diagnose, construct case conceptualizations, and plan psychotherapeutic treatment: a knowledge test and short case studies in a first study, and a complex, dynamically evolving case study in the second study. In our cross-sectional studies, psychology students, trainees in a certified postgraduate psychotherapist curriculum, and behavior therapists with more than ten years of experience were tested (100 in total: 20 each of novice, intermediate, and advanced university students, postgraduate trainees, and therapists). Clinical knowledge and competences increased up to the level of trainees but unexpectedly decreased at the level of experienced therapists. We discuss the results against the background of expertise research and the training of clinical psychologists (in Germany). Essential factors for continuing education of psychotherapists are proposed.